Digital Marketing Strategy on a Café During the Recovery from the Covid-19 Pandemic - Suwarno; Arief Fernando (Institute of Computer Science (IOCS), 2022)
The current Covid-19 pandemic has resulted in a decline in buying and selling activities. Some cafes have suffered material and immaterial losses, others have experienced massive layoffs, and others have gone bankrupt. In this case, the right digital marketing strategy is needed to deal with a deteriorating situation. This study aims to determine the effect of implementing digital marketing strategies through social commerce on cafes during the recovery period from the Covid-19 pandemic. This study uses a qualitative and quantitative approach. Interviews were conducted with two cafe managers in the city of Batam. The questionnaire is distributed using a disproportionate random sampling technique. The results show that Social media marketing, Brand Sense Scape, and Brand Service Scape significantly influence Brand Loyalty with an index of 92.8%, which can be concluded as a good category.